Implementation of the E-Performance Application Policy at the Office of the Class II Port Operator Unit of Bulukumba - Faruq, Ahmad Ilham; Jamaluddin, Jamaluddin; Isgunandar, Isgunandar (Pendidikan Administrasi Perkantoran, UNM, 2025)
The E-Performance application is one of the innovations in personnel management that aims to improve the efficiency and accountability of civil servant performance. The implementation of e-Performance applications in various government agencies is an important concern to ensure the effectiveness of the policies implemented. This research focuses on the implementation of the e-Performance application policy at the Bulukumba Class II Port Operator Unit Office, as well as identifying the driving and inhibiting factors for its implementation. This study applies a qualitative method by collecting data through observation, interviews, and documentation. The research informants involved five people, namely the Head of Office, the Administrative Officer of the Personnel Section, and other Civil Servants who played a direct role in this regulation. This research indicates that the implementation of the E-Performance application policy is still relatively ineffective. Some of the indicators that affect the effectiveness are: (1) good enough communication in conveying policy objectives and procedures, so that employees understand their roles; (2) limited resources, especially in terms of the availability of experts and training for employees; (3) positive disposition of employees and leaders, which contributes significantly to the success of implementation; and (4) a well-defined organizational structure and clear procedures in facilitating the implementation of policies. However, the study also identified challenges, such as age factors and health conditions of some employees, that hindered their ability to adapt to the new system. This condition shows that despite the potential for success; the implementation of the E-Performance application still requires improvements in terms of human resources and technical support. In conclusion, the implementation of the E-Performance application policy requires a holistic approach that considers technical and human factors to increase the effectiveness and efficiency of its implementation at the Bulukumba Class II Port Operator Unit Office.